1985
DOI: 10.1099/00207713-35-2-189
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter mucosalis (Lawson, Leaver, Pettigrew, and Rowland 1981) comb. nov.: Emended Description

Abstract: Seven strains of Campylobacter sputorum subsp. mucosalis, reference strains of Campylobacter fetus, Campylobacter jejuni, Campylobacter coli, Campylobacter laridis, "Campylobacter hyointestinulis, " ' 'Campylobacter fecalis, " C. sputorum subsp. sputorum, C . sputorum subsp. bubulus, and Campylobacter nitrofigilis, aerotolerant Campylobacter sp. strain 02790, and catalase-negative or weakly catalase-positive strain CG-1 were compared with C. sputorum subsp. mucosalis type strain NCTC 11000 in deoxyribonucleic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 19 publications
(17 reference statements)
2
19
0
Order By: Relevance
“…Furthermore, Smibert listed a third subspecies of C. sputorum, C. sputorum subsp. mucosalis (16), which had been described and named by Roop et al (29,30) as a separate species. These authors also showed that V .…”
mentioning
confidence: 99%
“…Furthermore, Smibert listed a third subspecies of C. sputorum, C. sputorum subsp. mucosalis (16), which had been described and named by Roop et al (29,30) as a separate species. These authors also showed that V .…”
mentioning
confidence: 99%
“…These oxidase-positive, catalase-negative bacteria were found to constitute a separate DNA relatedness group and were therefore removed as a subspecies of C. sputorum and given status as a separate species (145). The characteristics of C. mucosalis and its close relationship to C. concisus have been investigated in detail by Roop et al (144,145) and Tanner et al (166,167). C. mucosalis requires hydrogen or formate (from which it produces hydrogen) as an electron donor for growth.…”
Section: "C Upsaliensis"mentioning
confidence: 99%
“…Mter addition of the test substrates, dispensing, steriziliation and inoculation we carried out incubation under microaerophilic conditions at 42 °C. The isolated strains were identified according to the latest edition of Bergey's Manual (Krieg and Holt 1984) and in the light ofthe published data on newly accepted campylobacters (Benjamin et al 1983;Gebhart et al 1985;McClung et al 1983;Neil et al 1985;Roop et al 1985;Steele and Owen 1988;Tanner et al 1981 andTotten et al 1985). See Table 1.…”
Section: Methodsmentioning
confidence: 99%